Neurocognitive Assessment in the Diagnosis of HIV-Associated Neurocognitive Disorders - Robertson, Kevin; Yosief, Sarah (Seminars in Neurology, 2014)
Neurocognitive assessment plays a central role in the diagnosis of human immunodeficiency virus- (HIV) associated neurocognitive disorders (HAND). The history of diagnostic categories and labeling of HIV-related neurological disorders is briefly presented. The current diagnostic nomenclature of HAND and the role of neurocognitive assessment is examined. Though neurocognitive testing is sensitive in assessing a broad range of cognitive impairments, neurocognitive testing is not specific to HAND without consideration of the impact on functional status, as well as confounding factors, including premorbid status.
Keywords: human immunodeficiency virus; HIV-associated neurocognitive disorder; neuropsychological; HIV-associated dementia